2004
DOI: 10.1007/s00125-004-1396-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 12-month physical activity counselling intervention on glycaemic control and on the status of cardiovascular risk factors in people with Type 2 diabetes

Abstract: Aims/hypothesis. The aim of this study was to investigate the effectiveness of physical activity counselling in promoting physical activity in people with Type 2 diabetes and to evaluate resultant physiological and biochemical effects. Methods. A total of 70 inactive people with Type 2 diabetes were given standard exercise information and randomised to receive physical activity counselling (n=35, experimental) or not (n=35, control). Physical activity consultations were delivered at baseline and after 6 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
40
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(40 citation statements)
references
References 41 publications
0
40
0
Order By: Relevance
“…The three articles written by Kirk et al [44,45,47] were all based on the same study and, therefore, treated as one publication. Although these three papers were focussing on different research questions, they essentially used the same set of data for the parameters of interest for this review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The three articles written by Kirk et al [44,45,47] were all based on the same study and, therefore, treated as one publication. Although these three papers were focussing on different research questions, they essentially used the same set of data for the parameters of interest for this review.…”
Section: Resultsmentioning
confidence: 99%
“…Completed studies where individuals or groups were followed up in time and where the effects of interventions on physical activity were investigated totalled 21 studies: two completed RCTs focussing on arthritis [26,27], four completed RCTs focussing on COPD [2831], five RCTs focussing on CVD [3234,36,37], and ten completed studies focussing on Diabetes [3849] (where [44,45,47] were treated as being one study). The remaining studies were either published study protocols or presenting base line data only.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jonker JT et al [50] 2006 Prospective cohort study 5209 Moderately and highly active people have a longer total life expectancy and live more years free of diabetes than their sedentary counterparts but do not spend more years with diabetes. Kirk A et al [33] 2004 Randomized control trial 70 Physical activity counseling was effective in promoting physical activity in people with type 2 diabetes. The counseling improved glycemic control as well as the status of cardiovascular risk factors in these patients.…”
mentioning
confidence: 99%
“…For example, in a randomized controlled trial from the UK (n= 70), Kirk et al [33] conducted an intervention of physical activity counseling at baseline and after 6 months in women and men with type 2 diabetes. The authors reported that physical activity, total accelerometer counts/week, and blood glucose control (HbA1c) improved marginally in the intervention group, while no significant changes were found in the control group.…”
mentioning
confidence: 99%